Transgression médiatique et provocations décadentes: La décadence comme comportement médiatique. - Vérilhac, Yoan (Nordlit, 2012)
The decadent and symbolist movements are deeply connected to the creation of media: newspapers, small reviews which make the promotion of the young poets and their original works. In the 1880’s, the decadent reviews use in a provocative way the codes and the media potentialities. However this provocative press is based on a double language (especially about the relationship with the public), and this contradiction generates a negative image in the popular press: the new generation of poets and writers appears to be a noisy group of « hoaxers ». Therefore, around 1890, when the new reviews grouped around the « symbolist » label define themselves a media identity, it is important for them to distance from decadent behaviours. The decadent moment of the mediatization of literature is thus indispensable to understand the history of connections between press and poetic avant-gardes.